New and little known pholcid spiders (Araneae: Pholcidae) from Laos - Yao, Zhiyuan; Li, Shuqiang (Zootaxa, 2013)
Fourteen new species belonging to five pholcid genera are reported from Laos: Belisana champasakensis sp. nov. (male), B. crystallina sp. nov. (male and female), B. gigantea sp. nov. (male and female), B. khanensis sp. nov. (male and female), B. lancea sp. nov. (male), B. martensi sp. nov. (male), B. tadetuensis sp. nov. (male), B. xiangensis sp. nov. (male and female), Calapnita longa sp. nov. (male), Khorata circularis sp. nov. (male and female), K. dupla sp. nov. (male and female), Pholcus arcuatilis sp. nov. (female), P. sublaksao sp. nov. (male and female) and Spermophora falcata sp. nov. (male and female). The genera Belisana and Spermophora are reported from Laos for the first time.